Web-based Interactive graph visualization - Halim, Aldo (Nanyang Technological University, 2022)
Graphs are mathematical structures capable of representing relationships between objects. However, these complex structures are not only used to model data. They are also used to solve real-world problems by utilizing graph algorithms. Thus, it is critical for students majoring in Computer Science to understand thoroughly the concept of graphs and graph algorithms. However, having a good understanding of graphs can be a difficult task for beginners since it has a steep learning curve. A major issue that learners may face is the visualization of graph algorithms. Due to the complexity of graph structure, it is difficult to mentally visualize a graph and apply an algorithm to it. To address this problem, a graph visualization tool that supports graph creation and algorithm visualization can be used to aid the learning process. Currently, there are several existing graph visualization tools. However, they are not beginner-friendly, either lacking the interactivity in building graphs or not providing sufficient algorithm visualization. In light of the current situation, this project aims to develop Graphit, which is a highly interactive web-based graph visualization tool. Graphit provides an interface for its users to interactively create their own graphs and visualize algorithms on them. On top of that, it also provides a platform for users to save, manage, and share graphs they created. All these functionalities supported in the application are developed with a goal in mind, which is to assist novice learners in understanding graph algorithms while also having the best learning experience.